Effects of wildfire on sea otter (Enhydra lutris) gene transcript profiles. Issue 1 (24th July 2014) - Bowen, Lizabeth; Miles, A. Keith; Kolden, Crystal A.; Saarinen, Justin A.; Bodkin, James L.; Murray, Michael J.; Tinker, M. Tim
Abstract Wildfires have been shown to impact terrestrial species over a range of temporal scales. Little is known, however, about the more subtle toxicological effects of wildfires, particularly in downstream marine or downwind locations from the wildfire perimeter. These down‐current effects may be just as substantial as those effects within the perimeter. We used gene transcription technology, a sensitive indicator of immunological perturbation, to study the effects of the 2008 Basin Complex Fire on the California coast on a sentinel marine species, the sea otter (Enhydra lutris). We captured sea otters in 2008 (3 mo after the Basin Complex Fire was controlled) and 2009 (15 mo after the Basin Complex Fire was controlled) in the adjacent nearshore environment near Big Sur, California. Gene responses were distinctly different between Big Sur temporal groups, signifying detoxification of PAHs, possible associated response to potential malignant transformation, and suppression of immune function as the primary responses of sea otters to fire in 2008 compared to those captured in 2009. In general, gene transcription patterns in the 2008 sea otters were indicative of molecular reactions to organic exposure, malignant transformation, and decreased ability to respond to pathogens that seemed to consistent with short‐term hydrocarbon exposure.